Trends in Gabapentin Use in Neonatal Intensive Care Units from 2005 to 2020 - Roberts, Annette G.; Kilpatrick, Ryan; Diaz, Lindsey D.; Benjamin, Scott; Espinoza Santiago, Athziry J; Jallow, Bubacarr; Monteith, Madison F.; Rumsey, Sarah; Clark, Reese H.; Zimmerman, Kanecia; Benjamin, Daniel K., Jr.; Greenberg, Rachel G. (American Journal of Perinatology, 2024)
This study aimed to analyze trends in gabapentin use in neonatal intensive care units (NICUs) and examine demographic characteristics, diagnoses, and concomitant medications associated with its use.Cohort study of 987,181 infants hospitalized in the NICU from 2005 to 2020.Eighty-five infants (<0.01%) received gabapentin. From 2009 to 2020, there was a 1,055% relative increase in gabapentin use (p < 0.01). The median birth weight was 2,160 g (25th, 75th percentiles: 875, 3,080 g) in gabapentin-exposed infants compared with 2,498 g (1,890, 3,210 g) in unexposed infants (p < 0.001). Over half (55%) of infants receiving gabapentin were born prematurely, 54% (n = 45) had chronic lung disease, 46% (n = 39) had gastrostomy tubes, and 34% (n = 29) had drug withdrawal syndrome; 49% (n = 42) and 27% (n = 23) received opioids and benzodiazepines, respectively.Use of gabapentin was rare but increased over time despite limited research on its safety and efficacy in infants, illuminating the need for further studies.
Keywords: cohort study; retrospective study; gabapentin; neonatal intensive care units; premature infants; gabapentin trends